Playing On: Re-staging the Passion after the Death of God - Klomp, Mirella, (Theology in Practice ;, 2021)
In what is often considered 'a society "after God"', millions of Dutch participate annually in a public multi-media performance of Christ's Passion. What to make of this paradox? In Playing On: Re-staging the Passion after the Death of God , Mirella Klomp offers a theological analysis of this performance and those involved in it. Working in an interdisciplinary fashion and utilizing creative interludes, she demonstrates how precisely this production of Jesus' last hours carves out a new and unexpected space for God in a (post-)secular culture. Klomp argues compellingly that understanding God's presence in the Western world requires looking beyond the church and at the public domain; that is the future of practical theology. She lays out this agenda for practical theology by showing how the Dutch playfully rediscover Christian tradition, and - perhaps - even God.